The evolution of cell types in animals: emerging principles from molecular studies - Arendt, Detlev (Nature reviews. Genetics, 2008)
Cell types are fundamental units of multicellular life but their evolution is obscure. How did the first cell types emerge and become distinct in animal evolution? What were the sets of cell types that existed at important evolutionary nodes that represent eumetazoan or bilaterian ancestors? How did these ancient cell types diversify further during the evolution of organ systems in the descending evolutionary lines? The recent advent of cell type molecular fingerprinting has yielded initial insights into the evolutionary interrelationships of cell types between remote animal phyla and has allowed us to define some first principles of cell type diversification in animal evolution.